COMPARATIVE ANALYSIS OF TRADITIONAL AFRICAN AND WESTERN PEACE BUILDING - TANKO SHAWULU PAUL PAUL; KINGSLEY PHILIPS NOYE; EMMANUEL ACHUS JAH (International Studies Journal)
Conflict is a two edge phenomenon that can instigate human creativity toward innovation with the aim of providing stability and peace; on the other side is the distractive role it provides to the society. African traditional methods of conflict resolution have lost its potency in recent times due to Western Methodology in conflict resolution and its interference with African Philosophical approach. However, traditional African conflicts resolution mechanism is still relevant, as the Western concept is not providing the answers to peace. It is however imperative that both the traditional African conflict resolution mechanism and the Western Model are fused together in order to provide a conflict resolution in the African environment. Hence both the traditional African method and the Western style method still live with us and peace is what everyone need. This essay is an attempt to harmonize the Africa traditional conflict resolution and western methods of peace building in conflict management in the African environment with specific touch on the IGBO of the South East Nigeria and the BUEM of Ghana . peace building theory was used. Data were collected from both primary and secondary sources.